Penggunaan Instagram pada Generasi Z Sebagai Media Komunikasi dalam Membangun Personal Branding Ilustrator @Indahoei - Zain, Azizah Aghniya; Dwivayani, Kadek Dristiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The rapid development of the times gave birth to communication in the digital world and the creation of various kinds of social media applications, one of which is Instagram. Instagram is a place for users to share photos and videos as well as share stories and interactions so that its users are used to build personal branding. Personal branding is a place for an individual to be able to shape his or her identity by showing personality and expertise which ultimately creates a public perception. Personal branding can be done on Instagram, where Instagram users are dominated by Generation Z. Various professions now need personal branding. Various professions now need personal branding, including illustrators. Indah Wijaya is one of the illustrators in Indonesia with the Instagram account name @Indahoei. This research aims to find out how the use of Instagram in Generation Z as a communication medium in building personal branding for illustrator @Indahoei. In this study, researchers used the theory of uses and gratifications. This research method uses descriptive qualitative methods and data collection techniques by conducting observations, interviews, and documentation. Based on the results of the study, the researcher found that Indah uses Instagram to generate income and show her work that will make the audience recognize so they want to use her services. Indah applies the concepts of personal branding that make her try to remain consistent and maintain her good name. Indah realizes that the content she uploads on Instagram inspires her followers, so Indah always tries to create quality content that can be enjoyed properly.